2018
DOI: 10.1261/rna.067090.118
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte-specific maternal Slbp2 is required for replication-dependent histone storage and early nuclear cleavage in zebrafish oogenesis and embryogenesis

Abstract: Stem-loop binding protein (SLBP) is required for replication-dependent histone mRNA metabolism in mammals. Zebrafish possesses two , and is necessary for retinal neurogenesis. However, the detailed expression and function of in zebrafish are still unknown. In this study, we first identified zebrafish as an oocyte-specific maternal factor and then generated a maternal-zygotic F3 homozygous mutant (MZΔ4) using CRISPR/Cas9. The depletion of maternal Slbp2 disrupted early nuclear cleavage, which resulted in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
2
11
1
Order By: Relevance
“…RT-PCR revealed expression of slbp2 in the ovary, during the cleavage stage, and at 4 hpf (sphere stage), a post-MBT stage (Fig 8C). Comparably, slbp1 expression was detected at all corresponding stages (Fig 8C), consistent with previous data that also showed slbp1, but not slbp2 expression at later embryonic and larval stages [43,44]. Loss of zygotic Slbp1 function in the zebrafish leads to normal early embryonic development, but causes retinal developmental defects by 2 dpf, in addition to other morphological defects by 3 dpf [44].…”
Section: Screeching Halt Encodes Stem Loop Binding Proteinsupporting
confidence: 91%
See 1 more Smart Citation
“…RT-PCR revealed expression of slbp2 in the ovary, during the cleavage stage, and at 4 hpf (sphere stage), a post-MBT stage (Fig 8C). Comparably, slbp1 expression was detected at all corresponding stages (Fig 8C), consistent with previous data that also showed slbp1, but not slbp2 expression at later embryonic and larval stages [43,44]. Loss of zygotic Slbp1 function in the zebrafish leads to normal early embryonic development, but causes retinal developmental defects by 2 dpf, in addition to other morphological defects by 3 dpf [44].…”
Section: Screeching Halt Encodes Stem Loop Binding Proteinsupporting
confidence: 91%
“…Interestingly, knockdown of SLBP in dsRNA transgenic mouse oocytes also leads to an early developmental arrest, and the phenotype is rescued by injecting histone protein [45]. Recently, He et al, employed a reverse genetics approach to examine the function of zebrafish SLBP2 by generating indel alleles using CRISPR-Cas9 [43]. Interestingly, they demonstrated partial rescue of a chromatin phenotype in the arrested embryos (also reported in srh mutants, [13]) by introducing an H2B transgene into the mutant background.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Its expression levels were decreased gradually with the progress of spermatogenesis, which is consistent with the expression pattern of vasa in the male germ cells of gibel carp [22] and brown-marbled grouper [18]. As an oocyte-specific marker [19,23], slbp2 was used to distinguish the female germ cell and male germ cell. The non-expression of slbp2 in four cell types indicated that targeted cells didn't contaminate by female germ cells.…”
Section: Discussionsupporting
confidence: 71%
“…To understand the effects of histone concentration on the MBT we reduced maternally supplied histones by downregulating the gene encoding a crucial histone regulator, Stem-Loop Binding Protein (Slbp) (Sullivan et al, 2001;Dominski et al, 2002;Lanzotti et al, 2002;Iampietro et al, 2014;Lefebvre et al, 2017;He et al, 2018) via maternally driven RNAi (Perkins et al, 2015). Under these conditions, histone H2B was reduced by ∼50% and H3 by ∼60% at the MBT (Fig.…”
Section: Histone Concentration Regulates the Timing Of The Mbtmentioning
confidence: 99%